Predicting post‐breakup distress and growth in emerging adulthood: The roles of relationship satisfaction and emotion regulation. (9th January 2018) - Norona, Jerika C.; Scharf, Miri; Welsh, Deborah P.; Shulman, Shmuel
ABSTRACT: With a sample of emerging adults ( N = 110; 72% female) this brief report utilized self‐report measures to examine the role of relationship satisfaction and emotion regulation strategies assessed at age 20 in predicting breakup distress and posttraumatic growth three years later. Results showed that higher relationship satisfaction is associated with less future breakup distress. Emotion regulation explained the ways individuals cope with distress; cognitive appraisal (in contrast to emotional suppression) predicted higher growth after experiencing a breakup. Findings highlight the ways emotion regulation strategies can help emerging adults cope with relational stressors such as breakups.